Single component organic photosensitizer for tumor Photodynamic/Photothermal immunotherapy via apoptosis and pyroptosis - Miao-Yan Xu; Jie Zeng; Xin-Hao Han; Duo-Duo Wei; Bing Fan; Xin‑Hui Qu; Shaorong Huang; Xiao-Jian Han (Materials & Design)
Pyroptosis is the programmed cell death of inflammation and an effective way to eliminate tumors. However, how to trigger the pyroptosis of tumor cells is a great challenge. Herein, a JNC nanoparticles (NPs) synchronous shared fluorescence imaging (FLI), oxygen-dependent reduction type Ⅰ photodynamic therapy (PDT) and high-efficiency photothermal therapy (PTT) were prepared. Furthermore, JNC NPs + Laser has excellent tumor killing ability in vitro and in vivo. The mechanism of cell death induced by JNC NPs + Laser was closely related to mitochondrial apoptosis and pyroptosis. Moreover, JNC NPs + Laser can induce immunogenic cell death (ICD) to improve the maturation of dendritic cells (DCs) and present antigens to T cells, which high-effectively eliminate tumor lung metastasis. This finding provided a single component organic photosensitizer for tumor photodynamic/photothermal immunotherapy via apoptosis and pyroptosis.